2011
DOI: 10.1128/jvi.05639-11
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Nucleotide Inhibitors PSI-352938 and PSI-353661 Exhibit a Novel Mechanism of Resistance Requiring Multiple Mutations within Replicon RNA

Abstract: PSI-352938, a cyclic phosphate nucleotide, and PSI-353661, a phosphoramidate nucleotide, are prodrugs of ␤-D-2-deoxy-2-␣-fluoro-2-␤-C-methylguanosine-5-monophosphate. Both compounds are metabolized to the same active 5-triphosphate, PSI-352666, which serves as an alternative substrate inhibitor of the NS5B RNA-dependent RNA polymerase during HCV replication. PSI-352938 and PSI-353661 retained full activity against replicons containing the S282T substitution, which confers resistance to certain 2-substituted nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 30 publications
3
40
0
Order By: Relevance
“…This loop reordering may be critical to the transition from de novo initiation with GTP to the elongation of the growing primer-template RNA. Intriguingly, this same loop reordering was observed in the 2.5-Å structure of an apo 2a JFH1 isolate HCV NS5B resistance-derived triple mutant (S15G/C223H/V321I) (19) in which the ␤-hairpin loop is extant (unpublished data). The comparison of the apo 2a ⌬8 structure to other RdRp ternary complexes (12,15,44) suggested that in this open conformation, HCV NS5B is able to bind primer-template RNA.…”
Section: Resultsmentioning
confidence: 69%
“…This loop reordering may be critical to the transition from de novo initiation with GTP to the elongation of the growing primer-template RNA. Intriguingly, this same loop reordering was observed in the 2.5-Å structure of an apo 2a JFH1 isolate HCV NS5B resistance-derived triple mutant (S15G/C223H/V321I) (19) in which the ␤-hairpin loop is extant (unpublished data). The comparison of the apo 2a ⌬8 structure to other RdRp ternary complexes (12,15,44) suggested that in this open conformation, HCV NS5B is able to bind primer-template RNA.…”
Section: Resultsmentioning
confidence: 69%
“…Subtype-dependent resistance has previously been reported for the NS3 protease and nonnucleoside NS5B inhibitors (27). Recently, we reported that nucleotide prodrugs of 2=-F-2=-C-methylguanosine monophosphate, PSI-352938 and PSI-353661, were able to select for resistant mutations in the JFH-1-derived replicons but not in GT 1a and 1b replicons due to differences in fitness caused by the amino acid changes (15).…”
Section: Genotype Coveragementioning
confidence: 99%
“…Among the various NS5B mutations, we included representative amino acid changes (C316Y, M414T, M423T, P495L) that conferred resistance to the four main classes of NNIs (12), the S96T/N142T substitutions that conferred resistance to the 4=-azidocytidine nucleoside R1479 (1), the S282T substitution which conferred resistance to 2=-C-methylnucleosides/tides (29) and 2=-F-2=-C-methylpyrimidines (18,40), the S15G/C223H/V321I (JFH-1 GT 2a) changes that in combination conferred resistance to 2=-F-2=-C-methylguanosine analogs (15), and the F415Y (GT 1a) alteration that has previously been found in patients treated with ribavirin (47). As summarized in Table 2, the replicons with the C316Y, M414T, M423T, and P495L changes remained fully susceptible to the inhibition of PSI-7977, while showing a 26-to 70-fold reduction in sensitivity for the corresponding class of NNIs.…”
Section: Genotype Coveragementioning
confidence: 99%
“…In addition, variants NS5B S96T and N142T appear to be compensatory mutations for S282T in the replicon (39). The passaging of the 2=-methylguanosine inhibitor PSI-352938 did not readily select for variants in a genotype 1 replicon system; however, variants NS5B C223H/Y and V321I were selected after multiple passages in a genotype 2a replicon (J6/JFH-1), conveyed a 2.1-to 3.7-fold-decreased susceptibility, and are included in this analysis, but resistance Ͼ2-fold in genotype 1b was only conveyed by the combination of variants which had a significant impact on viral fitness (40). The NS5B S96T, N142T, C223H/Y, and S282T variants were not observed as the dominant viral population in any patients in the present study, and the NS5B V321I variant was observed in 0.19 and 2.51% of subtype 1a and 1b patients, respectively (Table 3).…”
Section: Baselinementioning
confidence: 99%